Enhanced thermal and hydrophobic surface properties of shape-stabilized nanodiamond/fatty alcohol grafted poly(ethylene-alt-maleic anhydride) composite phase change materials - KAHRAMAN, MEMET VEZİR (WILEY, 2018)
Fatty alcohol grafted poly(ethylene-alt-maleic anhydride) (PEMA-g-FA) are synthesized from esterification of poly (ethylene-alt-maleic anhydride) (PEMA) with tetradecanol and octadecanol. Obtained PEMA-g-FA's composites were prepared with different ratios of nanodiamond as phase change materials (PCM).The chemical structure of the synthesized PEMA-g-FA was investigated by Fourier transform infrared spectroscopy. Phase change behaviors of PEMA-g-FA and their composites were examined by using differential scanning calorimetry. Thermal stability of the samples was evaluated by thermogravimetric analysis. Moreover, the surface morphology of the samples was investigated by a scanning electron microscopy and atomic force microscope. The melting and freezing temperature and enthalpy of comb-like polymers were increased with increasing the content of nanodiamond and the n-alkyl side chains length. Finally, the obtained results prove that, thanks to high latent heat storage capacity and high thermal stability, the prepared comb-like polymeric PCMs and their composites could be used in thermal energy storage applications. The prepared shape stabilized composite PCMs could be a promising material and could have practical applications in industries such as solar cooling refrigeration systems, solar air heating systems, and smart textile systems. POLYM. COMPOS., 39:1887-1895, 2018. (c) 2016 Society of Plastics Engineers
Keywords: ENERGY STORAGE; MATRIX COMPOSITES; CONDUCTIVITY; POLYMER; FIBERS